2003
DOI: 10.1053/jvet.2003.50059
|View full text |Cite
|
Sign up to set email alerts
|

Healing characteristics of deep digital flexor tenorrhaphy within the digital sheath of horses

Abstract: Without improved methods for immobilizing the deep digital flexor tendon, intrathecal tenorrhaphy is unlikely to result in first intention tendon healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…A larger gap results in prolonged healing and a larger area of inferior collagen or scar tissue within the tendon. This results in delayed and inferior acquisition of strength of the repair than what would occur if primary healing were achieved because of altered mechanical characteristics of the tissue 2–7 . Gap formation occurs because of the inability to provide a repair with the strength to withstand tensile loads during weight bearing with or without external coaptation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A larger gap results in prolonged healing and a larger area of inferior collagen or scar tissue within the tendon. This results in delayed and inferior acquisition of strength of the repair than what would occur if primary healing were achieved because of altered mechanical characteristics of the tissue 2–7 . Gap formation occurs because of the inability to provide a repair with the strength to withstand tensile loads during weight bearing with or without external coaptation.…”
mentioning
confidence: 99%
“…Autologous tendon grafts combined with suture techniques have also been evaluated, 7 as have bioabsorbable implants and plates 11–13 . To date there is no combined suture material–repair technique described in vivo that prevents gap formation, even with external coaptation of the lower limb 4–6 …”
mentioning
confidence: 99%
“…Breeds included Quarter Horse (n = 164), Paint (59), Thoroughbred (38), Arabian (27), Standardbred (16), Tennessee Walking Horse (10), warmblood (8), Appaloosa (7), Miniature (7), pony (7), Saddlebred (7), draft (6), mule (6), Morgan (4), Missouri Fox Trotting Horse (3), and Peruvian Paso (2); breed was not recorded for 27 horses. One hundred eighty-three horses were treated at Purdue University, 114 horses were treated at the University of Missouri, 81 horses were treated at Iowa State University, and 20 horses were treated at the University of Georgia.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, 9 57 of 70 (81%) horses with a half-limb cast developed cast sores, which was higher than the percentage of horses with a TC in the study reported here that developed a cast sore. 16,17 Such fetlock joint extension may be prevented via application of casts to limbs in a flexed position. Those investigators may have been more likely to detect cast sores than were clinicians who evaluated horses with routine clinical problems in the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a gap with a mean value of 3.2 mm was present at the final follow-up in 24 of 34 repaired FDP tendons in zone II [24]. Gap healing following flexor tendon injury and repair has also been observed in animal models [20,22,25]. Delivery of new cells directly to the injury site could therefore be a useful therapeutic strategy both to accelerate healing and reduce the risk of late gapping.…”
Section: Discussionmentioning
confidence: 99%